The influence of cross-section variation on bending stiffness assessment in existing timber structures. (1st February 2020) - Osuna-Sequera, Carlos; Llana, Daniel F.; Íñiguez-González, Guillermo; Arriaga, Francisco
Highlights: 21 150 × 200 × 11, 000 mm 3 Salzmann pine rafters from 18th century building were analysed. Criteria were established to assign the most adequate nominal cross-section dimension. NDT measurements were used to optimize the nominal size dimensions assignment. Central area cross-section showed the best MOE estimation with ToF methods. Global mean cross-section showed the best MOE estimation with vibration analysis. Abstract: The frequent highly irregular geometry of the elements in existing timber structures complicates the structural verification of members and influences the use of non-destructive testing (NDT), affecting the inspection time, cost and results obtained. This process therefore needs to be improved. The main aim of this paper is to analyse how to obtain a representative nominal cross-section (NCS) of members, and its influence on determination of the static modulus of elasticity (MOEsta ). 21 150 × 200 × 11, 000 mm 3 Salzmann pine ( Pinus nigra subsp. salzmannii (Dunal) Franco) timber rafters from the 18th century Royal Coliseum of Charles III theatre (in Aranjuez, Madrid, Spain) were acoustically tested (by ultrasound, stress wave and vibration). The MOEsta was determined by mechanical testing, and different criteria for determining the NCS were analysed. Good correlation was obtained between the MOEsta and NDT parameters, and the best criterion to assign NCS was proposed to improve the accuracy of the models obtained by reducing the number of NCS measurements.